Numerical Solution of Ordinary Differential Equations of Fractional Order Using Variable Step Size Method - Fadhel, Fadhel S; Khayoon, Hayder H (Al-Nahrain Journal of Science, 2018)
The main objective from this paper is to introduce and derive three methods depending on fractional Euler’s method and improve the results modifying the approach by using variable step size method.